There Is a Systemic Problem Deeper than the Decolonizing and Anti-racism Movements Acknowledge Faithful Anti-Racism: Moving Past Talk to Systematic Change, Christina Edmondson, and Chad Brennan, IVP, 2022 (978-0-8308-4723-5), x + 238 pp., hb 25 Decolonizing Christianity: Becoming Badass Believers, Miguel A. De La Torre, Eerdmans, 2021 (ISBN 978-0-8028-7847-2), viii + 232 pp., hb 24.99 - Anderson, Owen (Reviews in religion and theology, 2023)
In these two books, the authors give solutions to disparities they trace to systemic racism. The De La Torre book especially examines how the Trump presidency solidified white Christianity. He argues that white Christians deify Trump and are therefore rejected by God. In the Edmondson and Brennan book, we are told that material disparities between races can only be explained by systemic racism. The authors then explain what we must do to repent of and overcome systemic racism. Both books are built on assumptions traceable to Marx and Nietzsche, neither gives us a robust augment against the best alternative explanations, and their use of the Bible only superficially treats categories like ‘believer/unbeliever’.